2021
DOI: 10.3389/fonc.2021.717989
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Genetic Alterations Stratified Prognosis in Oriental Pancreatic Cancer Patients

Abstract: BackgroundPancreatic cancer is a life-threatening malignant disease with significant diversity among geographic regions and races leading to distinct carcinogenesis and prognosis. Previous studies mainly focused on Western patients, while the genomic landscape of Oriental patients, especially Chinese, remained less investigated.MethodsA total of 408 pancreatic cancer patients were enrolled. A panel containing 436 cancer-related genes was used to detect genetic alterations in tumor samples.ResultsWe profiled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“… 19 , 20 , 21 Recently, studies have reported the genomic characteristics of Chinese pancreatic cancer patients, however, lack of blood paired germline or based on small cases, which is difficult to reflect the real-world genomic characteristics of pancreatic cancer from China. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 , 21 Recently, studies have reported the genomic characteristics of Chinese pancreatic cancer patients, however, lack of blood paired germline or based on small cases, which is difficult to reflect the real-world genomic characteristics of pancreatic cancer from China. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…REG4 overexpression was associated with poor prognosis and resistance to gemcitabine treatment in one study, suggesting that adjuvant therapies that target reg4 could enhance the usual gemcitabine-based treatment of pancreatic cancer [75,116,117]. ASAP2 (2p25.1) amplification has been associated with lower overall survival (OS) as well as lower relapse-free survival (RFS) [134,135]. FHIT (3p14.2) and ATR (3q23) deletions were mostly reported in both sporadic familial cases, indicating their possible role in PDAC susceptibility as well as progression [77,110,118,133,136].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ASAP2 (2p25.1) amplification has been associated with lower overall survival (OS) as well as lower relapse-free survival (RFS) [ 134 , 135 ]. FHIT (3p14.2) and ATR (3q23) deletions were mostly reported in both sporadic familial cases, indicating their possible role in PDAC susceptibility as well as progression [ 77 , 110 , 118 , 133 , 136 ].…”
Section: Cnv Studies In Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al. 4 profiled the genomic alteration of PDAC with 408 Chinese patients, showing a relatively higher mutation rates of DNA damage repair-related genes.…”
mentioning
confidence: 99%